Evaluación de cuatro dosis del Fertilizante F305G en el cultivo de soya (Glycine max (L) Merril) en suelo alcalino del Huallaga Central. - Reátegui Del Castillo, Maribel (2003)
The effect of smaller elements application over the yield of the Soy beans in an alkaline soil from Central Huallaga with automated seeder using different doses F305G fertilizer applied to the soil in of 20, 40, 60, 80 Kg/Ha concentrations comparing with a witness without any micronutrients application was evaluated in this thesis work, with the purpose of determining the economically more efficient dose to be recommended for producing Soy the farmers of the study area, in this way, to enlarge our region agricultural frontier. It was realized in Caspizapa district, Pioota County, Region San Martin, Regíon, distant to 73 Km from Tarapoto City, Arch. Femando Belaunde Terry Highway south, right side, Senorarca Sector, with soy IAC - 8 variety under tropical dry forest (td - F) conditions obtained production cost and benefit/cost relationship of different treatments, using the random totally blocks designs (RTSD). With 4 blocks and 5 treatments. The sow distancing among furrows was 0,45 m and 22 seeds for lineal meter. The obtained yields in different doses overcame the witness substantially, it was T4 with 4222,62; T2 with 3833,33; T3 with 3730,54; T5 with 3471,03 and the T1 with 3274,20 in yield order for Kg/Ha, comparatively with that of more yield and the witness it is a 948,42 Kg difference, close 1 TM.